Lynch Syndrome and MSI-H Cancers: From Mechanisms to “Off-The-Shelf” Cancer Vaccines - Roudko, Vladimir; Cimen Bozkus, Cansu; Greenbaum, Benjamin; Lucas, Aimee; Samstein, Robert; Bhardwaj, Nina (Frontiers in Immunology, 2021)
Defective DNA mismatch repair (dMMR) is associated with many cancer types including colon, gastric, endometrial, ovarian, hepatobiliary tract, urinary tract, brain and skin cancers. Lynch syndrome – a hereditary cause of dMMR – confers increased lifetime risk of malignancy in different organs and tissues. These Lynch syndrome pathogenic alleles are widely present in humans at a 1:320 population frequency of a single allele and associated with an up to 80% risk of developing microsatellite unstable cancer (microsatellite instability – high, or MSIH). Advanced MSIH tumors can be effectively treated with checkpoint inhibitors (CPI), however, that has led to response rates of only 30-60% despite their high tumor mutational burden and favorable immune gene signatures in the tumor microenvironment (TME). We and others have characterized a subset of MSIH-associated highly recurrent frameshift mutations that yield shared immunogenic neoantigens. These frameshifts might serve as targets for off-the-shelf cancer vaccine designs. In this review we discuss the current state of research around MSIH cancer vaccine development, its application to MSIH and Lynch syndrome cancer patients and the utility of MSIH as a biomarker for CPI therapy. We also summarize the tumor intrinsic mechanisms underlying the high occurrence rates of certain frameshifts in MSIH. Finally, we provide an overview of pivotal clinical trials investigating MSIH as a biomarker for CPI therapy and MSIH vaccines. Overall, this review will inform the development of novel research paradigms and therapeutics.